Performance Evaluation of DCF Length for High Scalability NG-PON2 - Brian Pamukti; Doan Perdana (Universitas Ahmad Dahlan, 2017)
Next Generation Passive Optical Network Stage 2 (NG-PON2) have to resolve the problem like demand each user, for example, HDTV, 3DTV, Hologram and Telemedicine. The research designed Passive Optical Network (PON), which is meet requirements of NG-PON2. Using stacked 4 Optical Line Terminal (OLT) with an aggregate 40 Gbps transmitted on fiber Single Mode Fiber (SMF) and Dispersion Compensation Fiber (DCF) by comparing the system without DCF cable. On the condition of minimum standards, the range of 40 km with a power splitter 1:64 only 9:01% power difference while the increased in the Q factor of 65.5%. With these results, it can be said that systems using DCF can be used optimally. In addition, with the power splitter 1: 4 and a lower power worth 0 dBm can produce a range of 150% further. With the same distance as far as 40 km, this research increasing power splitter 6 times increase compared with previous research.